2016
DOI: 10.31603/cakrawala.v11i2.249
|View full text |Cite
|
Sign up to set email alerts
|

Determinan Tingkat Efisiensi Perbankan Syariah Di Indonesia: Two Stages Data Envelopment Analysis

Abstract: Efficiency is an important indicator to observe the banks’ ability in resisting and facing the tight rivalry at banking industry. The study aims to evaluate the efficiency and to analyze the determinants of efficiency of Islamic bank in Indonesia on 2010 – 2013 with Two-Stage Data Envelopment Analysis approach. The objects of the study are 11 Islamic banks (BUS). The first phase of testing uses the Data Envelopment Analysis (DEA) method showed that the efficiency of Islamic bank is inefficient on managing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
21
1
19

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(50 citation statements)
references
References 0 publications
9
21
1
19
Order By: Relevance
“…Garza-García (2012) and Andries (2010) found the negative effect of NPL on the bank efficiency. This is not in line with Jaelani (2015) and Pambuko (2016) who found that NPL has the positive effect on the efficiency level. Adjei-Frimpong et al (2014) in his research found that NPL has no effects on efficiency.…”
Section: Introductioncontrasting
confidence: 65%
See 4 more Smart Citations
“…Garza-García (2012) and Andries (2010) found the negative effect of NPL on the bank efficiency. This is not in line with Jaelani (2015) and Pambuko (2016) who found that NPL has the positive effect on the efficiency level. Adjei-Frimpong et al (2014) in his research found that NPL has no effects on efficiency.…”
Section: Introductioncontrasting
confidence: 65%
“…ROA reflects the bank managing ability to produce the profits by using the finance assets provided efficiently (Jaelani, 2015), so that there is a positive relationship between ROA and efficiency. Adjei-Frimpong et al (2014), Hassan and Sanchez (2007), and Pambuko (2016) found the positive relationship between ROA and efficiency. Different from the above research, Muljawan et al (2014) found that ROA has no significant impact on efficiency.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations